2007
DOI: 10.1158/0008-5472.can-06-4183
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Underlying FIP1L1-PDGFRA–Mediated Myeloproliferation

Abstract: An interstitial deletion on chromosome 4q12 resulting in the formation of the FIP1L1-PDGFRA fusion protein is involved in the pathogenesis of imatinib-sensitive chronic eosinophilic leukemia. The molecular mechanisms underlying the development of disease are largely undefined. Human CD34 + hematopoietic progenitor cells were used to investigate the role of FIP1L1-PDGFRA in modulating lineage development. FIP1L1-PDGFRA induced both proliferation and differentiation of eosinophils, neutrophils, and erythrocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 32 publications
3
73
0
Order By: Relevance
“…The FIP1L1 portion is, however, a contributing factor to the higher proliferating activity, induced by FIP1L1-PDGFRA. This result is also consistent with a previous study, which shows that the FIP1L1 portion is necessary to activate STAT5 and the PKB/Akt pathway in human hematopoietic progenitor cells [8].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The FIP1L1 portion is, however, a contributing factor to the higher proliferating activity, induced by FIP1L1-PDGFRA. This result is also consistent with a previous study, which shows that the FIP1L1 portion is necessary to activate STAT5 and the PKB/Akt pathway in human hematopoietic progenitor cells [8].…”
Section: Discussionsupporting
confidence: 94%
“…A previous report indicated that disruption of the juxtamembrane domain of PDGFRA is critical for constitutive activation of the kinase, whereas the FIP1L1 portion is dispensable [7]. Recently, it has been found that the FIP1L1 portion is also necessary for activating STAT5 and PKB/Akt in human hematopoietic progenitor cells [8].…”
mentioning
confidence: 99%
“…Nevertheless, it is still the case that the FIP1L1-PDGFRA fusion gene is under control of the FIP1L1 promoter and translation start, and the FIP1L1 part in the fusion may determine the stability and subcellular localization of the fusion protein. Also, while FIP1L1 seems dispensable for transformation of Ba/F3 cells, Buitenhuis et al 64 documented the differences in in vitro colony formation between FIP1L1-PDGFRA transduced CD34 þ cells and cells transduced by a deletion variant lacking part of FIP1L1.…”
Section: Role Of Fip1l1mentioning
confidence: 99%
“…8,64 The exact mechanism, however, by which FIP1L1-PDGFRa preferentially affects eosinophils remains unclear. The essential role of FIP1L1-PDGFRA is clear from in vitro studies with the EOL-1 cell line, from mouse models of FIP1L1-PDGFRA induced disease, and from the remarkable responses of FIP1L1-PDFGRA-positive CEL patients to imatinib treatment.…”
Section: Role Of Fip1l1mentioning
confidence: 99%
“…As for the downstream signaling molecules, FIP1L1-PDGFR␣ was shown to activate STAT5, phosphatidylinositol 3-kinase, and Ras/ERK pathways like other LTKs, such as BCR-ABL, TEL-ABL, TEL-JAK2, and TEL-PDGFR␤ (18). In addition, Buitenhuis et al (22) recently reported that activation of phosphatidylinositol 3-kinase, ERK1/2, and STAT5 is pivotal for FIP1L1/PDGFR␣-induced myeloproliferation.…”
mentioning
confidence: 99%